Results from a randomized trial evaluating a hospital–school transition support model for students hospitalized with traumatic brain injury. (16th April 2018) - Glang, Ann; Todis, Bonnie; Ettel, Debbie; Wade, Shari L; Yeates, Keith Owen
ABSTRACT: Objective : To evaluate the utility of the STEP model, a systematic hospital–school transition protocol for children hospitalized for TBI. Setting : Five children's hospitals in Colorado, Ohio, and Oregon. Participants : Hundred families of children with mild, complicated mild, moderate, or severe TBI. Design : Randomized controlled trial (RCT); participants were randomized while hospitalized to the STEP (a standardized hospital– school transition protocol for children treated for TBI) or usual care condition. Main Measures : Questionnaire about child's special education eligibility status, support services, and academic accommodations; Achenbach Child Behaviour Checklist (CBCL); Behaviour Rating Inventory of Executive Function (BRIEF); Child and Adolescent Scale of Participation (CASP); Child and Adolescent Scales of Environment (CASE) Results : There were no significant effects, indicating that STEP participants did not differ from usual care participants on any study outcome at one month post-discharge or at one-year follow-up. Conclusion : The lack of significant findings in this study does not imply that effective hospital-to-school transition programming is unnecessary. Rather, the findings raise important questions regarding timing and dosage/intensity of intervention, appropriate measurement of outcomes, and fidelity of programme delivery. The study highlights difficulties involved in the conduct of community-based RCTs in the paediatric TBI population.